Lady Víbora - processos de criação de uma personagem ficcional autobiográfica - Santa Fé, Ilda Aparecida Ribeiro de (2019)
In this research I developed a fictional character called "Lady Víbora", based on my own autobiography. At the same time I tried to reflect on the different media in which the character came to life: engraving, fanzine, watercolor and virtual support (social networks). This research has as a methodology, the production and use of notebooks or artist diaries, where the steps that permeate the identification of the personality and the visual image that expresses and externalize "Lady Víbora" have been mapped.